Necessary changes in industrial relations - Hillery, Brian (Statistical and Social Inquiry Society of Ireland, 1980)
Industrial relations in Ireland may be characterised as a multiplicity of practices, some good and some bad, but all integrated in so far as they are founded on a set of fundamental principles which are themselves the product of an historical process going back over 100 years. Foremost among these principles is free or voluntary collective bargaining which continues to be the primary means of negotiations on pay and conditions between unionised employees and employers.
Symposium on Necessary Changes in Industrial Relations
Read before the Society, 13 December 1979
Keywords: Irish industrial relations; Collective bargaining; Strikes; Wage negotiation; 314.15